Pemanfaatan Ekstrak Biji Feun Kase (Thevetia peruviana) sebagai Inhibitor Korosi Logam Seng dalam Media HCl - Matius Stefanus Batu; Maria Magdalena Kolo; Adolvina Kono (Jurnal Riset Kimia, 2022)
Feun Kase seed extract can be used as a corrosion inhibitor on zinc metal in HCl solution. This study aims to determine the secondary metabolites contained in Feun Kase seed extract, inhibition efficiency and corrosion rate, and surface morphology of zinc metal in the inhibition process using Feun Kase seed extract in HCl media. Feun Kase seed extract was obtained by maceration extraction using methanol. In the corrosion inhibition test, the concentration and temperature variations were carried out to determine the effect on the inhibition efficiency and the corrosion rate per year. The results showed that the methanol extract of Feun Kase seeds contained secondary metabolites of alkaloids, flavonoids and saponins. The optimum inhibition efficiency was obtained at an inhibitor concentration of 30 ppm of 82.70% with a corrosion rate of 5.80 mm/year and at a temperature of 35ºC of 75.84% with a corrosion rate of 7.28 mm/year in the test of increasing the temperature of the corrosion medium. The morphological analysis of the zinc plate using the SEM instrument showed that the zinc plate without surface treatment (not immersed in HCl media) was still smooth. This is indicated by the surface of the zinc plate which is still clearly visible because it has not been affected by the corrosion medium. The zinc plate when immersed in HCl media, is damaged which is indicated by the presence of pores or holes. Zinc plate when added with Feun Kase seed extract in HCl media, the zinc surface was damaged but the damage was not as prominent as in HCl media without using an inhibitor.